Increased hormone activity promotes silk development and heat tolerance during the floret differentiation stage in maize - Huiqin Wang; Jing Sun; Hao Ren; Bin Zhao; Yuting Li; Zishan Zhang; Baizhao Ren; Aziz Khan; Jiwang Zhang; Yinglong Chen; Peng Liu (Crop Journal)
Heat stress, a major challenge in modern agriculture due to global warming, significantly reduces crop productivity. To mitigate its adverse effects on maize yield, it is crucial to understand the mechanisms by which heat stress impacts reproductive development. This study investigated the impact of heat stress during the 12th leaf (V12) stage, where silk development begins on grain yield formation, using heat-sensitive and heat-tolerant cultivars. Compared to pollen, silks were found to be more vulnerable to heat stress. Heat stress disrupted hormone balance and inhibited hormone signaling transduction pathways in silks, delaying silk emergence from bracts and reducing fertilization and grain yield. The heat-tolerant cultivar maintained silk growth by activating more response pathways, displaying faster hormone responses, and up-regulating hormones. Taken together, we propose that hormones play an essential role in silk development and later fertilization process.